2018
DOI: 10.3389/fpsyg.2018.00586
|View full text |Cite
|
Sign up to set email alerts
|

How Do High-Performance Work Systems Affect Individual Outcomes: A Multilevel Perspective

Abstract: Research on high-performance work systems (HPWS) has suggested that a potential disconnection may exist between organizational-level HPWS and employee experienced HPWS. However, few studies have identified factors that are implied within such a relationship. Using a sample of 397 employees, 84 line managers, and 21 HR executives in China, we examined whether line managers’ goal congruence can reduce the difference between organizational-level HPWS and employee experienced HPWS. Furthermore, this study also the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 73 publications
3
73
0
Order By: Relevance
“…As a result, managers should pay more attention to the implementation process when introducing HPWS into organizations. Research has suggested that supervisors' HR responsibility and goal congruence with their organizations are the pivotal factors facilitating their implementation efforts of HPWS (Whittaker and Marchington 2003;Zhang et al 2018). Thus, the implementation of HPWS should be included in a supervisor's job description.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…As a result, managers should pay more attention to the implementation process when introducing HPWS into organizations. Research has suggested that supervisors' HR responsibility and goal congruence with their organizations are the pivotal factors facilitating their implementation efforts of HPWS (Whittaker and Marchington 2003;Zhang et al 2018). Thus, the implementation of HPWS should be included in a supervisor's job description.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Zhang et al . () found a positive effect of HPWP on job satisfaction. In light of these results, and given our focus on job satisfaction, we follow the optimistic view, assuming that HPWPs are positively related to job satisfaction.…”
Section: Introductionmentioning
confidence: 92%
“…A number of studies in strategic human resource management (HRM) state that organizational performance is substantially supported by high‐performance work practices (HPWPs) (Huselid, ; Appelbaum et al ., ; Combs et al ., ; Saridakis et al ., ; Jiang and Messersmith, ). Recently, an increasing number of studies have addressed employee outcomes (e.g., job satisfaction, commitment, and turnover) in order to better understand the relationships between HPWPs and organizational performance (e.g., Van de Voorde et al ., ; Jiang et al ., ; Van de Voorde and Beijer, ; Ogbonnaya et al ., ; Hauff et al ., ; Ogbonnaya and Messersmith, ; Zhang et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Research has suggested that high-performance work system serves as an important component that enables organizations to become more effective and get competitive advantage (Zhang et al, 2018;Aryee et al, 2012;Toya et al, 2009;Bowen & Ostroff, 2004;Liao et al, 2009,). Highperformance work system (HPWS) refers to as the application of internally coherent, consistent and steady human resource practices intended in improving employee commitment, their competence as well as motivation (Aryee et al, 2012;Datta et al, 2005).…”
Section: Introductionmentioning
confidence: 99%